2020
DOI: 10.1177/0748233720912060
|View full text |Cite
|
Sign up to set email alerts
|

Impaired follicular development and endocrine disorders in female rats by prepubertal exposure to toxic doses of cadmium

Abstract: Cadmium (Cd) has been associated with several physiological problems including reproductive and endocrine system dysfunction resulting in temporary infertility. The principal objective of this project was to investigate the effects of prepubertal exposure to toxic doses of Cd on puberty onset, the endocrine system, and follicular development. For this purpose, 16 female Sprague-Dawley rats weaned on postnatal day (PND) 21 were randomly divided into 4 groups ( n = 4 per group). The treatments were as follows: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Excessive exposure to Cd, Pb, As, and Hg in the everyday environment may be toxic to human reproduction and development (9, 12-14). The main toxic effects of Cd, Pb, Hg, and As on the reproductive endocrine system comprise the promotion of oxidative stress, reduction of follicle-stimulating hormone, reduction of luteinizing hormone, reduction of follicular growth, promotion of follicular atresia and disruption of the estrous cycle (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive exposure to Cd, Pb, As, and Hg in the everyday environment may be toxic to human reproduction and development (9, 12-14). The main toxic effects of Cd, Pb, Hg, and As on the reproductive endocrine system comprise the promotion of oxidative stress, reduction of follicle-stimulating hormone, reduction of luteinizing hormone, reduction of follicular growth, promotion of follicular atresia and disruption of the estrous cycle (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Some animal studies have found a decrease in serum testosterone, estradiol, and progesterone following cadmium exposure, as well as increased lipid peroxidation and decreased antioxidant enzymes in the ovaries. 57 , 58 , 65 Others have reported an activation of steroidogenesis and increased serum estradiol and progesterone concentrations in the female offspring of cadmium-treated pregnant dams. 66 These conflicting results emphasize the need for further research on cadmium exposure and hormonal levels before and during reproductive maturation in large epidemiological studies with girls in the right developmental window.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 56 59 However, some of the experimental studies that administered cadmium orally have also reported later reproductive maturity in rats. 56 58 Later vaginal opening and an extended estrous cycle were observed in young females exposed after weaning 58 and in female offspring following exposure of the pregnant dams. 56 , 57 In contrast to the latter experimental studies, we did not observe any association between maternal erythrocyte cadmium during pregnancy and age at menarche.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accumulated that many factors, including abrupt changes in the breeding environment and hazardous feed additives, can cause aberrant follicular development and follicular atresia in laying hens [19][20][21]. Hg is the most toxic in various feeds and showed the serious risk to animal reproductive performance.…”
Section: Discussionmentioning
confidence: 99%